Exploring Fertilizer-Microbiome Interactions Through Next-Generation Sequencing (NGS): Insights for Sustainable Agriculture - Radzali, Mohamad Khairil bin; Amalia Mohd Hashim; Miratul Hada Mohd Ali; Wan Zuhainis Saad; Zakiah Anis Nawawi (Malaysian Journal of Science, 2025)
With the global demand for food production escalating, concerns about the long-term sustainability and environmental impact of traditional farming practices, particularly the application of chemical fertilizers, have gained prominence. Recognizing the importance of addressing these issues, this review explores the evolving dynamic between fertilizers and microbial communities, emphasizing the need for a more profound understanding of these interactions. The transformative impact of next-generation sequencing (NGS) technologies in unraveling microbial intricacies within agricultural ecosystems is highlighted as a crucial tool for advancing this understanding. Investigation extends to discerning the nuanced effects of both chemical and non-chemical fertilizers on soil microbiomes, considering variations in soil type and crop specificity. Linking these findings to the Sustainable Development Goals (SDGs), the review highlights the critical connection between fertilizer use, microbial diversity, and the achievement of sustainability objectives. Despite the potential of NGS, the review acknowledges current limitations, sparking discussions on potential technological advancements and methodological improvements. Emphasizing the necessity for interdisciplinary collaboration, it advocates for comprehensive insights that bridge gaps between microbiology, agriculture, and sustainability. In conclusion, the article synthesizes historical perspectives, cutting-edge technologies, and sustainable development objectives to provide a holistic understanding of the intricate interplay between fertilizers, microbial diversity, and the imperative path toward a more sustainable agricultural future.